QARAQALPAQ FOLKLORÍNDA ANEKDOT JANRÍ - Qalbaeva, G.S. (SCIENCE and SOCIETY, 2024)
The arcticle deals with the research of jangric pecularities and thematical directions of folk jokes in Karakalpak literary world. In the arcticle the jangric features are studied by means of uzbek, kazak folklore – study scientific traditions’ that exist up to-date. The whole material as the authors consider has a great scientific importance.